Combined Effects of Topdressing, Cultivation, and Carfentrazone-ethyl on Silvery-Thread Moss Infestation - Z. Raudenbush; S. Keeley (Kansas Agricultural Experiment Station Research Reports, 2015)
The greatest reduction in silvery-thread moss (STM;Bryum argenteumHedw.) cover was achieved when cultivation treatments were used in conjunction with carfentrazone.
Keywords: bentgrass; carfentrazone; cultivation; putting green; turfgrass; silvery-thread moss; topdressing